2012
DOI: 10.7453/gahmj.2012.1.1.016
|View full text |Cite
|
Sign up to set email alerts
|

Fever in Cancer Treatment: Coley's Therapy and Epidemiologic Observations

Abstract: In the fall of 1890, an athletic, self-possessed, and thoughtful 17-year-old girl, who had just returned from an adventurous trip to Alaska where she had hurt her hand in a trivial accident, went to see a young, innovative surgeon in his new practice in New York City. Barely out of Harvard Medical School, he was a rising star in New York surgical circles, and the young woman asked him for help with her poorly healing, swollen, and naggingly painful injury. This visit had a far-reaching effect on cancer researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 86 publications
0
40
0
1
Order By: Relevance
“…Of the 1200 documented patients he treated with Coley-Toxin 270 patients with nonoperable, often metastasized, cancer reportedly went into complete remission [97, 98]. In fact, about 80% of the reported spontaneous remissions from cancer are found to be related to infections [99] and the connection between febrile infection and spontaneous tumor regression is the most frequent association found in literature [86, 100–105].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 1200 documented patients he treated with Coley-Toxin 270 patients with nonoperable, often metastasized, cancer reportedly went into complete remission [97, 98]. In fact, about 80% of the reported spontaneous remissions from cancer are found to be related to infections [99] and the connection between febrile infection and spontaneous tumor regression is the most frequent association found in literature [86, 100–105].…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression, in turn, may also facilitate opportunistic infections that may lead to M1 type macrophage polarization. In accordance with these data, infections might indeed be associated with spontaneous tumor regression [194]. The hypothesis is further supported by observations that gut flora is crucial for an effective chemotherapy [195].…”
Section: Therapeutic Interventions Targeting Tams and Mdscs Tuninmentioning
confidence: 59%
“…However, its use was first reported back in the late 19th century, when surgeon William Coley demonstrated that the injection of killed bacterial products into inoperable sarcoma tissue led to the shrinkage of tumor [41]. He subsequently developed a mixed bacterial vaccine and was able to achieve long-term remissions in some patients with sarcoma and various tumor types [42, 43]. It was later recognized that cancer cells express tumor antigens that may stimulate cellular and/or humoral responses.…”
Section: Immunotherapymentioning
confidence: 99%